Effects of sex hormones on action potential and contraction of guinea pig papillary muscle - Zhang Yi; Hao Yong-Chang; Song Li-Lin; Guo Shu-Mei; Gu Shuang-Zhen; Lu Shen-Gui (Acta Pharmacologica Sinica; Vol 19, No 3 (May 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of sex hormones, estradiol (Est), progesterone (Pro) and testosterone (Tes) on the action potential (AP) and contraction of guinea pig papillary muscle. METHODS: Using conventional glass microelectrode and mechanical recording of myocardial contraction. RESULTS: Est slowed down the maximal rate of rise of phase 0 (Vmax) of AP at low concentration (1 mumol.L-1). At 10 mumol.L-1 and above, Est also prolonged AP duration (APD50 and APD90), effective refractory period (ERP) and decreased the maximal isometric tension (Pmax) and velocity of tension development (dT/dt) of contraction. Tes (100 mumol.L-1 - 1 mmol.L-1) prolonged APD90 and ERP with decreased Pmax and dT/dt. But Pro (1 mumol.L-1 - 1 mmol.L-1) had no effects on both AP and contraction. CONCLUSION: Est prolonged AP and depressed contraction of guinea pig papillary muscle.